Hubungan Paparan Sinar Matahari dan Aktivitas Fisik dengan Pertumbuhan Remaja di SMP Negeri 3 Banjarmasin - Vidia Nasya Nalurita; Mariani Mariani; Evy Noorhasanah; Noor Isna Tauhidah (Universitas Malahayati Lampung, 2026)
ABSTRACT Adolescence is a period of growth characterized by rapid physical development, particularly in height and changes in body composition. Environmental factors such as sunlight exposure and physical activity play an important role in supporting the growth process through vitamin D synthesis and stimulation of growth hormones. Insufficient sunlight exposure and suboptimal physical activity may negatively affect optimal adolescent growth. This study aimed to determine the relationship between sunlight exposure and physical activity with adolescent growth at SMP Negeri 3 Banjarmasin. This study employed a quantitative analytic design with a cross-sectional approach. The sample consisted of 89 adolescents selected using proportional stratified random sampling. Sunlight exposure was measured using the Sunlight Exposure Questionnaire (SEQ), physical activity was assessed using the International Physical Activity Questionnaire (IPAQ), and adolescent growth was evaluated based on height-for-age (HFA) and body mass index-for-age (BMI-for-age) indicators. Data analysis was conducted using univariate and bivariate analyses with the Spearman Rank test. The results showed a significant relationship between sunlight exposure and adolescent height (p = 0.000; r = 0.802), indicating a very strong and positive correlation. Sunlight exposure was also significantly associated with body mass index (p = 0.017; r = 0.252), demonstrating a moderate and positive correlation. In addition, physical activity was significantly related to adolescent height (p = 0.011; r = 0.269) and body mass index (p = 0.018; r = 0.251), both indicating moderate and positive correlations. Sunlight exposure and physical activity have a significant relationship with adolescent growth at SMP Negeri 3 Banjarmasin. Adequate sunlight exposure and optimal physical activity play an important role in supporting height growth and nutritional status among adolescents. Keywords: Sunlight Exposure, Physical Activity, Adolescent Growth. ABSTRAK Masa remaja merupakan periode pertumbuhan yang ditandai dengan percepatan pertumbuhan fisik, terutama tinggi badan dan perubahan komposisi tubuh. Faktor lingkungan seperti paparan sinar matahari dan aktivitas fisik memiliki peran penting dalam menunjang proses pertumbuhan melalui sintesis vitamin D dan stimulasi hormon pertumbuhan. Kurangnya paparan sinar matahari dan aktivitas fisik yang tidak optimal dapat berdampak pada pertumbuhan remaja yang kurang optimal. Penelitian ini bertujuan untuk mengetahui hubungan paparan sinar matahari dan aktivitas fisik dengan pertumbuhan remaja di SMP Negeri 3 Banjarmasin. Penelitian ini menggunakan desain kuantitatif analitik dengan pendekatan cross-sectional. Sampel penelitian berjumlah 89 remaja yang dipilih menggunakan teknik proportional stratified random sampling. Paparan sinar matahari diukur menggunakan Sunlight Exposure Questionnaire (SEQ), aktivitas fisik menggunakan International Physical Activity Questionnaire (IPAQ), dan pertumbuhan remaja dinilai berdasarkan indikator tinggi badan menurut umur (TB/U) dan indeks massa tubuh menurut umur (IMT/U). Analisis data dilakukan secara univariat dan bivariat menggunakan uji Spearman Rank. Hasil penelitian menunjukkan terdapat hubungan yang signifikan antara paparan sinar matahari dengan tinggi badan remaja (p = 0,000; r = 0,802) yang menunjukkan hubungan sangat kuat dan positif. Paparan sinar matahari juga berhubungan signifikan dengan indeks massa tubuh remaja (p = 0,017; r = 0,252) dengan kekuatan hubungan cukup dan positif. Selain itu, aktivitas fisik berhubungan signifikan dengan tinggi badan remaja (p = 0,011; r = 0,269) serta dengan indeks massa tubuh (p = 0,018; r = 0,251), yang menunjukkan hubungan cukup dan positif. Paparan sinar matahari dan aktivitas fisik memiliki hubungan yang signifikan dengan pertumbuhan remaja di SMP Negeri 3 Banjarmasin. Paparan sinar matahari yang cukup dan aktivitas fisik yang optimal berperan penting dalam mendukung pertumbuhan tinggi badan dan status gizi remaja. Kata Kunci: Paparan Sinar Matahari, Aktivitas Fisik, Pertumbuhan Remaja.